Concomitant Intraductal Papillary Mucinous Neoplasm in Pancreatic Ductal Adenocarcinoma Is an Independent Predictive Factor for the Occurrence of New Cancer in the Remnant Pancreas. Issue 5 (May 2020) - Matsuda, Ryota; Miyasaka, Yoshihiro; Ohishi, Yoshihiro; Yamamoto, Takeo; Saeki, Kiyoshi; Mochidome, Naoki; Abe, Atsushi; Ozono, Keigo; Shindo, Koji; Ohtsuka, Takao; Kikutake, Chie; Nakamura, Masafumi; et al.
Abstract : Objective: To determine the factors predicting the subsequent development of pancreatic ductal adenocarcinoma in remnant pancreas (PDAC-RP) after partial pancreatectomy for PDAC. Summary Background Data: PDAC-RP after partial pancreatectomy for PDAC is currently not so rare because of improved prognosis of PDAC patients due to recent advances in surgical techniques and adjuvant therapy. However, the predictive factors related to PDAC-RP remain unknown. Methods: We retrospectively reviewed the clinicopathological data of a consecutive series of 379 patients with PDAC treated by partial pancreatectomy between 1992 and 2015; 14 patients (3.69%) had PDAC-RP. Clinicopathological variables were compared between PDAC-RP and non-PDAC-RP. Results: In univariate analysis, concomitant intraductal papillary mucinous neoplasm (IPMN) ( P = 0.0005), cancer location (body/tail) ( P = 0.0060), and lower T factor in UICC ( P = 0.0039) were correlated with PDAC-RP development. Multivariate analysis revealed concomitant IPMN ( P = 0.0135) to be an independent predictive factor for PDAC-RP. PDAC concomitant with IPMN had higher cumulative incidence of PDAC-RP (47.5%/10 yrs) than PDAC without IPMN (9.96%/10 yrs) ( P = 0.0071). Moreover, the density of pancreatic intraepithelial neoplasia lesions in the background pancreas of cases of PDAC concomitant with IPMN (1.86/cm 2 ) was higher than that of cases of PDAC without IPMN (0.91/cm 2 ) ( P = 0.0007). Conclusions: Concomitant IPMN in PDAC is an independent predictive factor for the development of new PDAC in remnant pancreas. Cancer susceptibility of remnant pancreas after resection for PDAC concomitant with IPMN is probably due to an increased density of pancreatic intraepithelial neoplasia lesions. Abstract : Supplemental Digital Content is available in the text